IPTEKS PROSES BISNIS KEUANGAN PADA PT. PLN (PERSERO) UNIT INDUK WILAYAH SULUTTENGGO - Hutagalung, Ignatius Ramot; Mongi, Caesar Junior; Warongan, Jessy D.L (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT. PLN (Persero) as a State Company engaged in electricity business in Indonesia. Meanwhile PT. PLN (Persero) Unit Induk Wilayah Suluttenggo is a branch unit for North Sulawesi, Central Sulawesi and Gorontalo region. The business of PT. PLN (Persero) is a monopoly market making the company obligated to take care of everything in electricity field. The business is growing rapidly, so that PT. PLN (Persero) has to keep up with the existing development. Therefore PT. PLN (Persero) is having a lot of business cooperation with many different Vendors. Before doing a cooperation, both the PT. PLN (Persero) and Vendor made a contract. After the works is done by the Vendor, the Vendor will send a bill to a User. The User will then proceed it. The process named as Financial Business Processes.Keywords : Financial Business Processes, Electricity Business